Samobójstwo to nie wyjście - program antysuicydalny dla młodzieży = Suicide is'nt an option - antisuicide program for young people - Borowiec, Justyna (Vilnius: Mykolas Romeris Universitetas)
Prophylactic educational program for young people aiming counteraction occurrence of suicide phenomenon. The program comprises of description process of suicid behaviour formation, risk factors and protective factors. The program also includes the individual timetable for young people, parents and teachers.
Keywords: prophylactic educational program; young people; suicidal ideation; suicide; anti-suicide (suicide prevention) program; timetable; risk factors; protective factors; program profilaktyczno-edukacyjny; młodzież; suicydalność; program antysuicydalny; harmonogram zajęć; samobójstwo; czynniki ryzyka; czynniki chroniące